PLASTICINE AS AN EDUCATIONAL TOOL FOR CHILDRENS' FINE MOTOR SKILL DEVELOPMENT: A CASE STUDY - Iyar Sumiarsih; Tuharso; Nurkholis Majid (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
Fine motor skill is a fundamental aspect that must be trained from an early age to support children’s independence and school readiness. This study aims to determine the use of plasticine media in developing the children’s fine motor skills aged 4–5 years, and to find out the obstacles and solutions for teachers in the use of plasticine media to develop the children’s fine motor skills aged 4–5 years in Kober Al-Ikhlas Panawangan Ciamis. This study uses a qualitative method under a case study approach, at which the data collected through observation and in-depth interviews with teachers and parents. The results showed that using plasticine through a play-and-learn approach, from demonstration to self-exploration, was very effective in improving accuracy, finger muscle strength, and eye-hand coordination. At the same time, the primary challenges faced were time limitations and the varying baseline motor skills among the children, both of which contributed to physical exhaustion. Then, this obstacle is addressed through individualized assistance from teachers and the parents’ active involvement in continuing stimulation at home without pressure.